Suppression of Philadelphia1 leukemia cell growth in mice by BCR-ABL antisense oligodeoxynucleotide. - Skorski, T (1994)
When injected into SCID mice, the Philadelphia chromosome-positive chronic myeloid leukemia-blast crisis cell line BV173 induces a disease process closely resembling that seen in leukemia patients. At 1 and 3 weeks after injection of 10(6) BV173 cells, CD10+ cells were detected in the bone marrow of the mice, leukemic colonies grew from bone marrow and spleen cell suspensions, and BCR-ABL transcripts were detectable in bone marrow, spleen, peripheral blood, liver, and lungs. Systemic treatment of the leukemic mice with a 26-mer BCR-ABL antisense oligodeoxynucleotide (1 mg/day for 9 days) induced disappearance of CD10+ and clonogenic leukemic cells and a marked decrease in BCR-ABL mRNA in mouse tissues. Untreated mice or mice treated with a BCR-ABL sense oligodeoxynucleotide or a 6-base-mismatched antisense oligodeoxynucleotide oligodeoxynucleotide were dead 8-13 weeks after leukemia cell injection; in marked contrast, mice treated with BCR-ABL antisense oligodeoxynucleotide died of leukemia 18-23 weeks after injection of leukemic cells. These findings provide evidence for the in vivo effectiveness of an anticancer therapy based on antisense oligodeoxynucleotides targeting a tumor-specific gene.